A contradição/conflito entre formação cultural e indústria cultural em Theodor W Adorno - Schulz, Paulo Ricardo (2011)
The paper seeks to analyze the contradiction/conflict that emerges between the cultural formation and the cultural industry, considering as a start TW Adorno thoughts, and it points to education as the one which can contribute to the autonomy of the individual conscience who lives inside the capitalist society, land where flourishes the conflict between the cultural formation and the cultural industry. It's inquired to describe the cultural formation as result of dialectic development of human civilization. It's shown that the period of mythic human thought already had some rationality, since this period, when giving names to the unknown and formulating explanatory stories to natural phenomenons already sought to control the line of nature. The period of logical and rational thought arises, therefore, on one side, as mythical thought overcoming, because the technique, which is the essence of this knowledge, takes refuge with the Mathematics, formulas, rule and probability to destitute all and every evidence of myth. This rational and technical moment also preserves in itself, however, something of mythological, cause it starts to enrapture the number, the formulas and the rule, mental creations which are the substitutes of the concepts that guided the mythical period. Men when expressing their subjectivity and with the desire of dominating the nature, created the divinities as in mythical period as in rational period and, in both of them, the periods turned to adore the work of their own hands. The reason that is described as the agent of cultural formation, acts dialectically in two levels: Virstand/subjective and Vernunft/objective, however, due to the reason instrumentation, this dialectic hasn't maintained itself, and this was one of the factors that has hindered the cultural formation and consequently the subject majority and autonomy. The support of mythological character in a time considered completely enlightened can be evidenced by cultural industry. It´s through it where everything gets to be submitted to market fetishism and its demands. This industry is analyzed like the union of radio, television, cinema and ideology. It pursues to standardize everything around itself, aiming to turn everything into merchant, even people´s will and the education. The leisure and recreation are also manipulated and became mere entertainment which obliterated the imagination and reason. The cultural and education reduction to a semi culture (H albbi ldung ) lent to the cultural industry a cultural formation appearance, but that, in fact, is only a so-called formation. The education, inside this quarrelsome context, however, can collaborate significantly to the awareness and emancipation insofar it reestablishes a proper dialectic between subjective and objective reason. A centric challenge is, therefore, to evince the artifices,veils, torches and magics that, in an absolute light age, daily obstruct the critical and autonomous individuals formation . This way, even when not requiring the overcoming of current society to inside its limits, the education can be designed as a space of resistance, a refuge of freedom , able to contribute to subjects formation who can really make choices, think and act in a free way.